Righteous Lives : Narratives of the New Orleans Civil Rights Movement. - Rogers, Kim Lacy (NYU Press, 1992)
An emotionally evocative, richly textured history based on autobiographical accounts of those who lived and shaped the struggle. The importance of many of Rogers' subjects and the uniqueness of New Orleans make this must reading for anyone interested in the history of the movement. But those interested in oral history and African-American autobiography will find riches aplenty as well. A welcome addition to a number of literatures. -- Doug McAdam, author of Freedom Summer. Righteous Lives skillfully blends oral history with a perceptive analysis of three generations of civil rights leadership.